Evaluation of Normal Renal Size and its Influencing Factors: A Cross-Sectional Study on the Adult Population of Mashhad. - Masoud Pezeshki Rad; Bita Abbasi; Niloufar Valizadeh; Farbod Hatami; Fariba Tohidinezhad; Zahra Gharehbaghi (Babol University of Medical Sciences, 2022)
Background: The normal range of kidney size is a controversial issue among different populations given to its impressibility by multiple factors, therefore, this study aimed to provide valid reference ranges for kidney dimensions in the adult population of Mashhad. Also, we assessed the association of kidney size characteristics with some personal predisposing factors. Methods: This cross-sectional study was conducted on 938 healthy individuals. Ultrasound measurement, physical examination, and laboratory analysis were performed. Demographic, dietary, and anthropometric data were obtained. The variables were categorized into 5 groups each, and data analysis were performed using the following statistical tests: Pearson correlation test, variance analysis, t-test, and chi-square test. A value of p<0.05 was considered statistically significant. Results: Weight had the most association with kidney size followed to a lesser extent by height and age. Even after adjustment for other confounding variables, weight remained as an independent factor, while this effect was resolved for height and age. Also, all values for renal function, body bio-impedance, blood pressure components, and water intake were notably correlated with kidney size. Conclusion: This study determined the normal kidney size in healthy adults. We also declared the normal range of kidney size is a dynamic concept and should be assessed for each individual separately according to their personal determinative factors.